Disseminated Granulomatous Disease from Intravesical Instillation of Bacillus Calmette-Guerin - Ghafouri, Sayed Ab. Reshad (Case Rep Oncol Med, 2018)
Intravesical instillation of Bacillus Calmette-Guerin is one of the standard treatment options for superficial bladder cancer. While Bacillus Calmette-Guerin therapy is usually well tolerated with most patients experiencing only cystitis, in rare cases, it can lead to disseminated granulomatous disease. We present a case of a 72-year-old man with disseminated granulomatous disease from intravesical BCG instillation whose treatment was complicated by antimycobacterial drug toxicity.